واقع الطلاق في المجتمع الليبي دراسة وثائقية تحليلية (الجنوب الليبي نموذجاً) - يوسف محمد أبو القاسم الصيد (Scientific Journal of University of Benghazi, 2020)
Official statistics in southern Libya indicate that the reality of divorces has increased in varying proportions in different years, on this basis the study aimed to identify the reality of divorce in southern Libya, to reveal the extent of the phenomenon and to identify the reasons for it and the repercussions that may result from it, The study started from the most important questions (there is a rise in divorces in southern Libya from 2011-2019, and attribution of the reasons to early marriage and the high cost of living and the weakness of the economic situation and the association with foreigners, the size of the sample of the study (200) divorce incidents distributed in the regions of southern Libya, from the reality of Records and documents in the magistrates' courts, using the method (analytical survey) in the study of the problem from 2000-2019, the study reached a number of results, the most important of which is the rise of divorces in the city of Sabha in 2010 by 6.4%, (10.5%) Alshtie 2017(35.7%) In samnoo, (10.5%) In Obari, one of the reasons for divorce is the worst of the 10% The absence of the husband by (20%) One of the most serious consequences of divorce in southern Libya (psychological, social and economic pressures on women and the displacement of children.